EXCLUSION OF INDIVIDUAL RESPONSIBILITY BY INDONESIA – TIMOR LESTE COMMISSION FOR TRUTH AND FRIENDSHIP - Judhariksawan, Judhariksawan (Indonesian Journal of International Law, 2021)
In international criminal law, there is a general principle applied that no one may be held accountable for an act that he has not performed. In the history of international humanitarian trials, there is an additional principle that nobody may be held accountable for criminal offences perpetrated by another person. But, with mandate and conclusion of Commission for Truth and Friendship between Indonesia and Timor Leste, there is no individual responsibility for gross violation of human rights.